Management of Myzus persicae with leaves of Jatropha curcas and Ricinus communis in different vegetative stages - Holtz, Anderson; Stinguel, Priscila; Ataide, Julielson; Aguiar, Ronilda Lana; Piffer, Ana Beatriz Mamedes; Magnago, Ariana (Revista de Ciências Agroveterinárias, 2022)
Although chemical insecticides are successfully used in agriculture, several problems may be related to their indiscriminate use. This has encouraged the development of alternative methods for pest insect control and societal pressure for pesticide-free products. The jatropha (J. curcas) and castor bean (Ricinus communis) are plants that have shown insecticidal potential. Thus, the objective of this work was to study the effects of leaves of R. communis and J. curcas of different ages on the cabbage aphid (Myzus persicae). Five solution concentrations and five leaf types were used. Each treatment consisted of ten individuals M. persicae, kept in Petri dishes (10.0 x 1.2 cm), about kale leaf discs. Each Petri dish was considered a repeat, totaling ten. An airbrush connected to a compressor calibrated at constant pressure and 5 mL of solution per repetition was used for direct application. The cabbage discs were immersed in the different treatments for five seconds and offered to aphids in the indirect application. For both tests, evaluations were performed 72 hours after application. Data were submitted to linear regression analysis and means test. There was an interaction between the application type, leaf type, and concentrations for both plants. We argue that at their different ages, jatropha and castor bean leaves have insecticidal potential in the management of M. persicae.